POLISH-UKRAINIAN CULTURAL DIALOGUE OF THE 17th CENTURY AS A RESULT OF RELIGIOUS CONTROVERSY - Denysiuk, Vasyl (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction. In the imperial, Soviet and post-Soviet era, the formation of a negative core of religious polemics was observed, which became an obstacle to the intellectual development of the Ukrainian ethnic group. The Catholic faith, which the Poles professed, became for the Muscovites the tool that they actively began to use to oppose Catholicism and Orthodoxy, to promote the narratives of uniting Ukrainians with Muscovites into a single religious community, and hence the state. Purpose. The purpose of the article is the Polish-Ukrainian cultural dialogue, which ensured the entry of Ukrainians into the European cultural space of the 17th century. Methods. To achieve the declared goal, the main method of discourse analysis, as well as deductive, inductive, comparative, descriptive methods, was used. Results. The analysis of the works of historians, philosophers, religious scholars, and linguists gave grounds for the conclusion that the Ukrainian territory of the 17th century was a place where the interests of two great powers, which conducted foreign policies in different ways, collided: if the Polish-Lithuanian Commonwealth, trying to convert Ukrainians to Catholicism and the Polish language, unconsciously contribute to the intellectualization of Ukrainians, the Muscovites, after the participation of the Cossack troops under the leadership of P. Konashevich-Sahaidachny for the return of the crown of the Moscow tsar to Vladyslav IV Vasa, began activities aimed at splitting Ukrainian society, creating conflict situations between Ukrainians and Poles, which began to develop into uprisings or wars, which, in turn, reduced human resources and led to economic collapse. Originality. For Ukrainians, contacts with the Polish-Lithuanian Commonwealth in the 17th century, despite all the negative aspects, had many more advantages, in particular education (the opening of fraternal schools, which later grew into higher educational institutions; the Polish language as one of the languages of the educational space) and culture (borrowing from the Polish language / literature / culture or through it new genres, styles, penetration of contemporary European and world subjects into Ukrainian studies; enrichment of the lexical structure of the Ukrainian language; the role of the Polish language in displacing the Church Slavonic element from the living Ukrainian language; development grammatical thought and lexicography). Conclusion. The study of Ukrainian-Polish contacts, particularly in diachrony, is always timely. The noninvolved approach made it possible to clarify two lines of development of events: first, the reformation movements in the middle of the Polish-Lithuanian Commonwealth and the efforts of the Polish government to resolve this issue; secondly, neglecting the linguistic and religious interests of numerous peoples, in particular Ukrainians, made it impossible for them to fully join the Polish-Lithuanian Commonwealth.